(untitled) (Nordic Journal of African Studies, 2002)
In this article a measurement instrument for the degree of conjunctivism / disjunctivism of the South African languages is presented. Following a discussion on conjunctivism versus disjunctivism, both absolute and relative approaches towards this measurement instrument are experimented with. Three potential absolute instruments are derived: one based on word length, one on sentence length, and one on the standardised type/token ratio. All of them pose problems. The search for a relative instrument is more successful. Although large sets of parallel texts would provide the ideal data, two-by-two parallel corpora offer a good substitute. The final 11 x 11 array is also compiled in this way. Applications of the 11 x 11 array in several fundamental and applied linguistic fields are reviewed. The fields include translation, academic writing, corpus linguistics, and theoretical reflections about spellcheckers and multi-dimension dictionary Rulers. A complete Bantu Array could be the ultimate goal.